Optimal utilization of legume fodder banks and low quality roughages by grazing cattle. - Mani, R.I. (University of Melbourne, 1992)
Low feed quality, short periods of grazing each day and the need to search for forage are all constraints on cattle productivity in most parts of Africa. From the literature reviewed, it was observed that many factors affect the intake and utilization of feeds and that no single factor controls intake and/or utilization. Consequently, in the experiments in this thesis the effect of feed quality and limited time of access to the feed were investigated using stall-fed and grazing animals. The study determined the effect of these factors on the intake and utilization of legume forage supplement and low quality roughage. This was to provide a basis on which to develop a management strategy for using forage legume-based pastures (fodder bank) as a source of supplement for traditionally managed cattle maintained on the range. A series of experiments were undertaken to examine (a) the effect of restricted time of access to feed on intake and utilization; (b) the effect of feeding additional urea-molasses block on .?.? intake and utilization of low quality roughage and forage legume supplement; (c) the grazing pattern and forage selection of Bunaji cattle grazing open range or Stylosanthes-based fodder bank; (d) the growth and reproductive performance of Bunaji cattle maintained on open range, or supplemented on preserved natural pasture, or fodder bank with or without additional ureamolasses block. Results from a pen experiment on the effect of feedi ng straw and providing forage legume supplement for a limited time indicated that sheep were able to consume enough supplement to result in liveweight gain and wool growth even when daily access was limited to 0.5 hours. In another experiment, limiting total access to feed to only 9 hours per day and forage legume offered for only 1 hour per day resulted in low feed intake and performance of the animals maintained on the low quality roughage alone. This indicated that provided there is access to good feed even for a limited period, animals are able to adjust their rate of eating and feed intake to support improved performance. Feeding urea-molasses block containing 12.5% urea to provide non protein nitrogen (NPN) while animals were confined at night improved the intake of the low quality roughage in stall-fed cattle without access to forage legume supplement and increased the intake of the legume supplement in those with access to both, but did not improve digestible dry matter intake. The dry matter (OM) disappearance of the low quality roughages and the legume from nylon bags incubated in the rumen of both sheep and cattle were significantly improved by the forage legume supplementation. This was associated with increased rumen NHJ-N concentrations. Although additional feeding of urea-molasses block after confining animals at night increased rumen NH4-N concentration in cattle, it did not increase feed digestibility possibly because of lack of continuous supply of enough NH4-N in the rumen for continuous fermentation of fibrous feed components. The immediate interpretation was that, because the urea-molasses block was fed at night, most of the additional N was excreted in the urine. The relationship between time of N provision and continuing fibre fermentation was therefore complex and sensitive to timing. Data from the grazing experiment indicated that cattle compensated for the low N content of the common range grasses by preferentially feeding on crop residue and browse plants during the dry season. Thus they were not as' adversely affected as they would have been if they had to consume only available range grasses. Crop residue and browse plants were most important to the group that had no access to the forage 1egume fodder bank as supplement. The importance of browse plants increased as the dry season advanced. Animals in all groups were found to seek the regrowth of grasses from burnt areas of the range, especially at the onset of the rains when most of the Stylo ha